Whole-Genome Expression Analysis and Signal Pathway Screening of Synovium-Derived Mesenchymal Stromal Cells in Rheumatoid Arthritis - Jingyi Hou; Yi Ouyang; Haiquan Deng; Zhong Chen; Bin Song; Zhongyu Xie; Peng Wang; Jinteng Li; Weiping Li; Rui Yang (Stem Cells International)
Synovium-derived mesenchymal stromal cells (SMSCs) may play an important role in the pathogenesis of rheumatoid arthritis (RA) and show promise for therapeutic applications in RA. In this study, a whole-genome microarray analysis was used to detect differential gene expression in SMSCs from RA patients and healthy donors (HDs). Our results showed that there were 4828 differentially expressed genes in the RA group compared to the HD group; 3117 genes were upregulated, and 1711 genes were downregulated. A Gene Ontology analysis showed significantly enriched terms of differentially expressed genes in the biological process, cellular component, and molecular function domains. A Kyoto Encyclopedia of Genes and Genomes analysis showed that the MAPK signaling and rheumatoid arthritis pathways were upregulated and that the p53 signaling pathway was downregulated in RA SMSCs. Quantitative real-time polymerase chain reaction was applied to verify the expression variations of the partial genes mentioned above, and a western blot analysis was used to determine the expression levels of p53, p-JNK, p-ERK, and p-p38. Our study found that differentially expressed genes in the MAPK signaling, rheumatoid arthritis, and p53 signaling pathways may help to explain the pathogenic mechanism of RA and lead to therapeutic RA SMSC applications.